A new species of Isometopus Fieber, the first record of Isometopinae (Heteroptera: Miridae) from Thailand - Yasunaga, Tomohide; Yamada, Kazutaka; Artchawakom, Taksin (Zootaxa, 2013)
The isometopine plant bug genus Isometopus Fieber currently comprises 69 nominal species (Schuh, 1995). The majority of the members are known to occur in the Old World tropics, subtropics and warm temperate zone; 26 species have been reported from the Afrotropical Region, and Asian faunas documented mainly by Lin (2004) [Taiwan], Ren (1991) and Ren & Yang (1988) [China], Yasunaga (2001, 2005) [Japan], and Yasunaga & Duwal (2006) [Nepal]. However, there is no reliable account of the Isometopinae from Thailand, or Indochina.